Analysis of Prostate-Specific Antigen Examination Results Using the iChroma II Device at Pandan Arang Hospital Boyolali During July–September 2025 - Monika Putri Solikah; Mayasyah Adelia Putri; Puput Handayani; Inapoik Feroni Kelyau Tanody; Fikran Suneth (Rifa'Institute, 2026)
Introduction: Prostate-specific antigen is an important biomarker used in the early detection and monitoring of prostate disorders. Objective: This study aimed to identify the distribution of prostate-specific antigen examination results by age group, determine the proportion of normal and abnormal prostate-specific antigen levels, and analyze the relationship between age and prostate-specific antigen levels in male patients at RSUD Pandan Arang Boyolali. Method: This descriptive study was conducted at the laboratory of RSUD Pandan Arang Boyolali from July to September 2025 using purposive sampling. A total of 33 male patients aged more than 50 years with complete medical records were included. Prostate-specific antigen levels were measured using the iChroma II device. Result and Discussion: Most patients had prostate-specific antigen levels within the normal range (60.6%), while 18.1% had low levels and 21.2% had high levels. Patients with elevated prostate-specific antigen levels were 52 to 83 years old, and the highest values were found in older patients. These findings indicate an age-related tendency toward increased prostate-specific antigen levels. Conclusions: There was a relationship between increasing age and prostate-specific antigen levels among male patients examined using iChroma II at RSUD Pandan Arang Boyolali.